Hak Prerogatif Presiden Pasca Revisi Undang-Undang Kementerian Negara: Tinjauan Konstitusional dan Fiqh Siyasah - Ahamd Attaji, Musyafa; Mu’in, Fathul; Yasin al Arif, M. (Kartika: Jurnal Studi Keislaman, 2025)
The revision of Article 15 of Law No. 39 of 2008 through Law No. 61 of 2024, which removes the limit on the number of ministries, has caused academic concern regarding the potential concentration of executive power, which is contrary to the principle of checks and balances in Indonesia's presidential system. This study aims to analyze the legal implications of this revision on the president's prerogative rights and to examine the principles of fiqh siyasah dusturiyah as the ethical basis for limiting power. The research method uses a normative legal approach with descriptive-analytical analysis, combined with a conceptual and statute approach, as well as a fiqh siyasah dusturiyah approach that focuses on the principles of maslahah mursalah, 'adl, and syura. The results of the study show that removing the limit on the number of ministries has the potential to cause constitutional overreach because it weakens the legislative oversight function and opens up opportunities for patronage politics. The fiqh siyasah dusturiyah perspective emphasizes that the formation of ministries must be oriented towards the public interest, not pragmatic political interests. The integration of positive law and fiqh siyasah dusturiyah produces a constitutional ethics model that balances formal legality and the morality of power The implications of this study recommend limiting the president's prerogative rights through proportional, efficient, and public interest-oriented regulatory revisions.